Milkman - Burns, Anna (London Faber & Faber, 2018)
In this unnamed city, to be interesting is dangerous. Middle sister is our protagonist. She is busy attempting to keep her mother from discovering her nearly-boyfriend and to keep everyone in the dark about her encounter with Milkman
1
Keywords: Families -- Fiction; Secrecy -- Fiction